Chemical composition of leaf essential oil of Lantana camara L. from Bangladesh (Bangladesh Journal of Botany, 2008)
Essential oil of fresh matured leaves of Lantana camara L. growing in Bangladesh were analyzed by GC-MS technique. Sixty two compounds were identified in the oil. The major constituents identified include caryophyllene (13.57%), α-caryophyllene (11.76%), germacrene D (10.88%), isocaryo-phyllene (9.59%), Î³- muurolene (6.85%) and Î³-elemene (5.65%). Â  Key words: Lantana camara, Essential oil, Caryophyllene DOI = 10.3329/bjb.v36i2.1513 Bangladesh J. Bot. 36(2): 193-194, 2007 (December)